PENGARUH REGULASI DIRI TERHADAP PENYESUAIAN DIRI PADA SISWA PONDOK PESANTREN MA HUSNUL KHOTIMAH - Dwi Kencana Wulan; Widarti Ratna Negara (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2018)
The purpose of this study was to determine the effect of self-regulation to the adjustment. Measurement variable adjustment using a measuring instrument Student Adaptation to College Questionnaire (SACQ) and to the measurement of self-regulation variables using a measuring instrument ie Adolescent Self-Regulatory Inventory (ASRI). Data processing method used in this research is the method of regression analysis. The results of the research conducted is when the adjustment (Y) increases one unit, then the self-regulation variable (X) will be in increments of 0.82. It is concluded that there are positive influence of self-regulation to the adjustment. Variable self-regulation affects adjustment of 10% and the rest influenced by other factors outside of self-regulation.